2008
DOI: 10.2186/jjps.52.501
|View full text |Cite
|
Sign up to set email alerts
|

Ion Release from Casts of Commercially Pure Titanium in Mixed Solutions of Organic Acids Contained in Human Saliva

Abstract: Ions released from metals are an issue in regard to their biocompatibility. We immersed titanium in mixed solutions of organic acids contained in human saliva. The results suggest that titanium elutes in the oral cavity, and that it is, therefore, necessary to consider the possibility of allergic reactions to titanium. AbstractPurpose: The purpose of this study was to investigate the ion release from titanium casts in solutions of mixed organic acids and to reconsider the possibility of allergic reactions to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In this study, the results of the immersion tests demonstrated a remarkable decrease in the dissolution by adding Zr to Ti, indicating that a Ti‐Zr alloy would be inert and thus release extremely low levels of Ti ions into the human body. Although there have been very few reports addressing the toxicity of Ti ions to the human body, it would be better to minimize the dissolution of metal ions to reduce the risks related to allergic reactions . Thus, alloying Zr with Ti would be one method of reducing the corrosion risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the results of the immersion tests demonstrated a remarkable decrease in the dissolution by adding Zr to Ti, indicating that a Ti‐Zr alloy would be inert and thus release extremely low levels of Ti ions into the human body. Although there have been very few reports addressing the toxicity of Ti ions to the human body, it would be better to minimize the dissolution of metal ions to reduce the risks related to allergic reactions . Thus, alloying Zr with Ti would be one method of reducing the corrosion risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been very few reports addressing the toxicity of Ti ions to the human body, 31,32 it would be better to minimize the dissolution of metal ions to reduce the risks related to allergic reactions. 33,34 Thus, alloying Zr with Ti would be one method of reducing the corrosion risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, corrosive milieu proteins (e.g. albumin, α‐globulin, transferrin, and fibrinogen) and amino acids have a strong affinity for metal ions, and, because these elements are capable of forming metallo‐organic complexes, they will increase the corrosion rate of Ti alloys significantly . The most obvious evidence of Ti release or corrosion is a dark, probably harmless, tissue discolouration that has been reported in both stable and failed implants, owing to oxide produced after surface wear (Fig.…”
Section: Release Of Ti Ions From Metal Alloysmentioning
confidence: 99%
“…At present, plate dentures composed of a cobaltchromium alloy and zirconia framework for the palate are increasingly being used for improving the strength and compatibility of plate dentures. [13][14][15][16] Because of problems, such as allergy to cobalt-chromium alloy and titanium, [16][17][18][19][20] plate dentures with a zirconia framework for the palate are gaining attention. However, it is difficult to adjust these types of dentures by cutting after fabrication; therefore, during palate plate fabrication, it is important to identify the appropriate site that requires relief as well as the degree of relief that is required.…”
Section: Introductionmentioning
confidence: 99%